教師專業學習社群信念與教學效能之研究 Professional Learning Communities: Teachers' Beliefs and Teaching Efficacy - 連倖誼 Hsin-Yi Lien; 張雅筑 Ya-Chu Chang (National Changhua University of Education, 2017)
本研究旨在瞭解教師專業學習社群信念及其對教學效能之影響。以「教師專業學習社群信念及教學效能問卷」調查金門縣國小共19 所學校，264 位已參與教師專業學習社群之老師之參與信念及其教學效能。並以平均數、標準差、t 考驗、單因子變異數分析、皮爾 森積差相關及多元迴歸等統計方法進行資料分析。研究結果顯示國小教師對專業學習社群發展具有中高認同度，因「教育程度」、「現任職務」不同，而有顯著差異。對其教學效能表現為高度認同，因「服務年資」、「參加社群年資」不同，而有顯著差異。此 外教師專業學習社群信念與其教學效能之間呈正相關。且教師專業學習社群信念對教學效能具有正向的預測力。本研究分別對教育行政機關及學校行政提出具體建議。 This study aimed to explore teachers' beliefs about professional learning communities (PLCs) and how these affect their teaching efficacy. The research data were collected by means of a questionnaire from 264 teachers participating in professional learning communities in 19 schools in Kinmen County. Data were analyzed using descriptive statistics, t-test, one-way ANOVA, Pearson correlation coefficient and multiple regression analysis. The results showed that the teachers' opinions of professional learning communities in elementary schools in Kinmen County were in the range of medium to high. Significant differences were found in "education level" and "current job position." Teachers' efficacy was at a high level, and significant differences were found in "the length of teaching" and "the length of participating in a professional learning community". In addition, teachers' perceptions of professional learning communities were positively correlated with their teaching efficacy. Teachers' beliefs in regard to professional learning communities served as a predictor of their teaching efficacy. Based on the research results, this study proposes some suggestions for the educational administration institutions and schools' administration, respectively.